Users’ intention to self-archiving in institutional repositories - Asad, Shahla; Abdullah, Rusli; Jusoh, Yusmadi Yah (Science and Engineering Research Support Society, 2019)
The institutional repositories (IRs) are considered as a novel and substitute technology for scholarly communication and its usability mainly depend on the quantity of its content material, which obtainable with self- archiving of research output by authors.The proposed study aimed to examine which factors influence users‟ intention to self-archiving in IRs.The proposed study usedthe unified theory of acceptance and the use of technology (UTAUT) as its main theoretical framework and five hypotheses were proposed to investigate users intention to self-archiving in IRs. Data for this analysis were obtained from 177 Malaysian researchers and authors and the structural equation modeling (SEM) was employed to test the research model. The obtained results from SEM indicated that “attitude facilitating conditions, and social influence” have the statistically significant influence on users‟ intention to self-archiving and factors “effort-expectancy and performance expectancy” were not statistically significant for authors‟ intention to self-archiving in IRs. The findings of this studyprovide information regarding the most important factors that are vital for formulating an appropriate strategic model to acceptance of self-archiving in institutional repositories.